Zarządzanie proekologiczne truciznami występującymi w środowisku naturalnym: Eco-friendly management of poisons found in natural environment - Marciniuk-Kluska, Anna (Management and Administration Journal, 2021)
The study presents issues relating to eco-friendly management of poisons foundin the natural environment that cause its degradation. It also considers the main sources of pollution and ecological threats. Since a human being exists in the natural environment, we havetaken into account the influence of chosen poisons on a human body. Despite considerableecological awareness and education of the society, still substances, objects and poisons reachthe natural environment degrading it. Implementing proper directives by the European Unionand resolutions by the Minister of the Environment has a positive influence on the quality of theenvironment we all live in. Nonetheless, the fact that ecological threats exist is unchangeablyindisputable. When taking advantage of the benefits of the natural environment, one must remember about the principles of sustainable development.